DIGITAL CONCEPTUALITY OF PROFESSIONAL LEARNING IN TECHNOLOGY LESSONS - Kharlamenko, Valentyna; Dimnych, Yaroslav (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article is devoted to topical issues of digitalization of technology lessons in a specialized school. The purpose of the article is to analyze the possibilities of implementing digital technologies in the technology lessons in a specialized school. In the course of the research, we found out that the teachers of the specialized school are interested in conducting technology lessons by means of digitalization, which is indicated by the following presentation of the answers: students like technology lessons using digital technologies: very like - 71.3%, like - 25.4%, not very like - 3.3%, dislike - 0%; interesting technology lessons using digital equipment for: 54.7% - very interesting, generally interesting - 40%, not very interesting - 5.3%, dislike- 0%); how much is available for the presentation of the educational material and the course of practical work with the use of digital technologies: clear – 68.7%, fairly clear – 28.9%, not quite clear – 2.4%; to what extent the acquired skills and knowledge obtained in technology lessons with a digital concept are useful for further education: yes - 52.6%, mostly, but not all - 47.4% (32 respondents), not sure - 0%. It was established that due to possibility of digital technologies’ implementation into the educational process in technology lessons in a specialized school, students generate their own ideas, materialize them and acquire the anticipatory skills necessary for life in a digital society. Technology lessons organized using this approach allow the teacher to adapt his/her methods to the specific needs and challenges of today and the interests of the students.